2020
DOI: 10.1016/j.ajog.2019.11.1255
|View full text |Cite
|
Sign up to set email alerts
|

Achieving clinically meaningful response in endometriosis pain symptoms is associated with improvements in health-related quality of life and work productivity: analysis of 2 phase III clinical trials

Abstract: BACKGROUND: Endometriosis-related pain symptoms have a negative impact on health-related quality of life and productivity. In fact, as endometriosis-related symptom severity and the number of symptoms experienced increases, health-related quality of life decreases. Dysmenorrhea and nonmenstrual pelvic pain are prominent symptoms experienced by women with endometriosis and were shown to have improved with the oral, nonpeptide gonadotropin-releasing hormone antagonist, elagolix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
(37 reference statements)
2
29
0
1
Order By: Relevance
“…Although there are dissenting views, 28 recent studies support the use of this new, orally active modality. [29][30][31][32][33] The aim of this review is to provide a practical guide for use of elagolix based on available evidence and clinical experience. It is anticipated that with ongoing experience, expertise will continue to develop regarding the best use of pharmaceutical agents for the management of endometriosis symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are dissenting views, 28 recent studies support the use of this new, orally active modality. [29][30][31][32][33] The aim of this review is to provide a practical guide for use of elagolix based on available evidence and clinical experience. It is anticipated that with ongoing experience, expertise will continue to develop regarding the best use of pharmaceutical agents for the management of endometriosis symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that pelvic pain is more strongly associated with peritoneal macrophage dysfunction than the presence of active endometriosis lesions per se. Current treatment approaches for endometriosis focus on either surgical removal of disease or hormonal suppression of lesion growth but this does not improve pain symptoms in all women (22,33,34). Our new data suggest that divergence in pain responses may be influenced by the direct response of peritoneal macrophages to a given treatment.…”
Section: Discussionmentioning
confidence: 85%
“…For example, GnRH agonists are reported to reduce pelvic pain in women with endometriosis (35) and, notably, this treatment has been shown to increase PMφ cytotoxicity (36) and reduce peritoneal fluid concentrations of the pain-correlated cytokine IL6 in women with endometriosis (37). Large-scale clinical trials have shown that the non-peptide GnRH antagonist Elagolix has a clinically meaningful reduction in the pain domain of EHP30 but only in around half of the women tested (22,34). To the best of our knowledge, the impact of Elagolix on peritoneal macrophage function has not been investigated but baseline differences in peritoneal macrophage phenotype could account for some of the reported differences in pain response.…”
Section: Discussionmentioning
confidence: 99%
“…Dyspareunia, dysmenorrhea, and non-menstrual pelvic pain symptom severity were determined, and pain severity was recorded by patients throughout the study using an Endometriosis Daily Pain Impact eDiary, which consists of pain impact items and uses a scoring system that have both been validated, as previously described. 12,15,16 For dyspareunia, women were asked to choose the item that best described their pain during sexual intercourse during the last 24 hours. Options given for women to rank their dyspareunia were none (score 0, no discomfort during sexual intercourse), mild (score 1, I was able to tolerate the discomfort during sexual intercourse), moderate (score 2, intercourse was interrupted because of pain), severe (score 3, I avoided sexual intercourse because of pain), or not applicable (I was not sexually active for reasons other than my endometriosis or did not have sexual intercourse).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate to severe endometriosisassociated pain was based on the mean pain scores during the month before baseline in the self-reported Endometriosis Daily Pain Impact eDiary with endometriosis-associated pain diagnosed by the investigator, as described previously. 12,15,16 Women were randomized 3:2:2 to receive placebo, elagolix 150 mg once daily (150-mg cohort), or elagolix 200 mg twice daily (200-mg cohort), for 6 months with a 12-month follow-up period. The coprimary endpoints for both studies were the proportion of women who achieved a clinical response for dysmenorrhea and non-menstrual pelvic pain at month 3 of treatment.…”
Section: Methodsmentioning
confidence: 99%